Static Characterization of InAs/AlGaAs Broadband Self-Assembled Quantum Dot Lasers - D. Ghodsi Nahri; H. Arabshahi H. Arabshahi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
The static-characteristics of InAs/AlGaAs broadband self-assembled quantum-dot laser diodes (SAQD-LDs) have been studied to solve the rate equations numerically using fourth-order Runge-Kutta method. Energy level, size, and composition distributions of the InAs/AlGaAs broadband quantum-dots (QDs) are considered and their effects on Static-characteristics are investigated. Simulated results of static-characteristics show that nonlinearity appears in light-current characteristics whereas homogeneous broadening (HB) becomes equal to inhomogeneous broadening (IHB). Slope-efficiency increases as the HB heightens up to the IHB. Exceeding the HB from IHB results in degradation of light-current characteristics. In fact, InAs/AlGaAs broadband SAQD-LD has the best performance when HB is equal to IHB. Light-current characteristics degrade and threshold current increases as the IHB enhances. We also investigate the effects of QD coverage on the laser performance and show that there is an optimum QD coverage in which the SAQD-LD operates with lowest possible threshold current and maximum output power as whatever the QD coverage enhances from that optimum amount, the threshold current increases and slope efficiency decreases.